DIRECTIONS FOR DEVELOPING ENTREPRENEURSHIP AS THE ECONOMIC BASIS OF UZBEKISTAN (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The reforms being carried out to expand and develop entrepreneurial activity, one of the main pillars of the economic growth of the Republic of Uzbekistan, and their results are presented, and the problems arising during their activity are highlighted.